« MaT(i)erre(s) » : vers une architecture ? - Yann Nussaume; Antoine Kilian (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Faced with environmental changes and a breakdown in the relationship between architecture and place, many architects are turning to the redevelopment of “MaT(i)erre(s)”. By intersecting the trajectories of six architects active on this subject and by comparing their design processes, this article questions the emergence of an architectural "environmental movement" and attempts to define its characteristics. To do this, it considers the various pathways and questionings of these architects which led them to their interest in “MaT(i)erre(s)”, and discusses some of their common orientations: rethinking the role of material as a catalyst for design; reassessing the architect/craftsman's estrangement; and promoting experimentation and research. Reflecting upon the milieux, the “MaT(i)erre(s)' Environmental Movement” unleashes an “Esprit Nouveau”.